(untitled) (Politeja, 2025)
This exploratory study investigates hesitation towards voluntary enlistment in the military. It seeks to understand the generic underlying factors that deter individuals from enlisting in the military at a time when conscription is less practiced in some countries. By using a qualitative method that involves Google Form and selected follow-up interviews, the findings in this work suggest that hesitancy towards voluntary enlistment in the military stems from a variety of factors that can be intrinsic, conditional/extrinsic, and partly institutional. It also highlights that reluctance to enlist voluntarily in the military is often influenced in some individuals by the behaviors of serving or ex-soldiers and is mediated by the soldiers themselves or by third party platforms.